(untitled) (Fiep Bulletin - online, 2014)
Aging in the individual passes through several phases where changes occur both in the biological , psychological and social . Therapeutic exercise at this time of life have effects in improving muscle strength , endurance , coordination, self -esteem , and optimize quality of life . The study aimed to analyze the influence of therapeutic exercises in circuit the quality of life of the elderly through the application of the SF - 36 and specific objectives describe the application of therapeutic exercises in circuit for elderly and compare the quality of life before and after application of the exercises . The research was the type analytical , quantitative and intervention . Data collection began with the assent given by the Ethics Committee of the Hospital Dr. Carlos Alberto Studart held in three phases : in the first questionnaire was applied to assess the quality of life Short Form - SF -36 , in the second stage exercises were performed on the circuit , and in the last phase the reapplication of the questionnaire . A total of 10 elderly females aged between 60 and 70 years. The exercises were held two days a week in a church hall in the city of Fortaleza - Ceará , between July and August 2010 . The results focus on the improvement of the physical aspects to rise from 55 to 100 ; emotional : 76.67 to 100 ; social : 76.25 to 87.5 , and general condition / health : 55.8 to 58.5 points . Thus we can see the benefits of exercise for improving quality of life in elderly women . It is concluded that through therapeutic exercises were benefits in quality of life of the group investigated .